Asertividad y consumo de drogas en estudiantes mexicanos (2012)
The aim of this study was to assess the relationship between low assertiveness and illicit drug use among high school students, and to determine which of the assertive characteristics such as behavioral control, recognition and acceptance of others, effective coping with problems and interpersonal differences, perceived self-efficacy in problem solving, verbal expression skills and positive affect in dealing with problems, acted as predictors of consumption. The research used a non- experimental cross-sectional and ex post facto design. By means of a non-probabilistic sampling technique, 1492 high school students were selected from schools located in high risk areas for drug consumption and were surveyed through the Assertive Factors Assessment Scale [EFA for its Spanish acronym], validated with Mexican adolescent population. The students were divided in two groups, the Illicit Drug users and the Non-drug users. After comparing the assertive characteristics between both groups, it was found that Non-drug users have more effective strategies for coping with problems, a perception of higher self-efficacy in solving problems, higher behavioral control, greater recognition and acceptance of others, better verbal expression skills and a more effective emotional management. It also found by logistic regression analysis that behavioral control and recognition and acceptance of others were factors most likely to serve as protective factors of illicit drug use. Results confirm the importance of communication skills, impulse control and emotional management for establishing more satisfying relationships and coping with access to tobacco, alcohol or illicit drugs.